Pengembangan Aplikasi Weighing Scale Truck Digital dengan Python dan Codeigniter Berbasis WEB Menggunakan Metode Waterfall - Agung Maulana; Mochammad Faid; Widjianto (KLIK: Kajian Ilmiah Informatika dan Komputer, 2023)
In the increasingly advanced era of globalization, computer technology is utilized in various fields, including the construction sector. CV. Anugrah is a contracting company engaged in infrastructure and property development. One of the challenges faced by the company is the inaccuracy in manually recording the load quantities of mixer trucks, which can have a negative impact on the company's management and decision-making processes. Therefore, this research aims to develop a computerized weighbridge recording system using the Codeigniter framework and the Python programming language. In developing this application, research methods were employed, including data collection techniques such as observation, interviews, and literature reviews as the foundation. Subsequently, the software development method using the waterfall model approach was implemented. The waterfall model was chosen due to its classical characteristics with a linear system flow, where the output of each phase serves as input for the next phase. The result of this research is a web application that uses a computerized weighbridge with load cells as sensors. This application plays a role in recording and managing weighing data with improved accuracy and efficiency, thereby enhancing the efficiency and effectiveness of the company's management and decision-making processes